2018
DOI: 10.1051/0004-6361/201833104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inertia and roughness of the nucleus of comet 67P/Churyumov–Gerasimenko from MIRO and VIRTIS observations

Abstract: Aims. Using data from the Rosetta mission to comet 67P/Churyumov–Gerasimenko, we evaluate the physical properties of the surface and subsurface of the nucleus and derive estimates for the thermal inertia (TI) and roughness in several regions on the largest lobe of the nucleus. Methods. We have developed a thermal model to compute the temperature on the surface and in the uppermost subsurface layers of the nucleus. The model takes heat conduction, self-heating, and shadowing effects into account. To reproduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…With a value of 22 J K -1 m -2 s -1/2 , they check their modelled value against diurnal phase curves for the temperature and find good agreement between the data and model. Finally, Marshall et al (2018) also analyse data from September 2014 and calculate bounds for the thermal inertia in five spots on the nucleus surface. Results in the mm channel imply that the thermal inertia is <80 J K -1 m -2 s -1/2 .…”
Section: Miro Thermal Inertia Measurementsmentioning
confidence: 99%
“…With a value of 22 J K -1 m -2 s -1/2 , they check their modelled value against diurnal phase curves for the temperature and find good agreement between the data and model. Finally, Marshall et al (2018) also analyse data from September 2014 and calculate bounds for the thermal inertia in five spots on the nucleus surface. Results in the mm channel imply that the thermal inertia is <80 J K -1 m -2 s -1/2 .…”
Section: Miro Thermal Inertia Measurementsmentioning
confidence: 99%
“…67P exhibits a low surface albedo ∼ 4% , is dominated by organic materials and has an extremely high porosity Hérique et al 2016;Pätzold et al 2016Pätzold et al , 2019. These compositional and structural characteristics result in a low thermal inertia Marshall et al 2018), which promotes large temperature gradients over a few cm and extreme temperature swings following rapid changes in illumination. Little to no ice is directly detected on the surface, except: 1) in specific shadowed areas where ice can remain stable for extended periods of time (Filacchione et al 2016a), 2) as surface frost associated to a diurnal cycle where ice is mobilized from the subsurface during the day and then is recondensed on the surface during the night (De , and 3) when the activity level increased enough towards perihelion for nucleus erosion to expose fresher materials .…”
Section: General Characteristicsmentioning
confidence: 99%
“…For modeling such heat transfer processes, one has to know the thermal and mechanical properties of the materials involved. Rosetta instruments (MIRO, VIRTIS, OSIRIS, RSI, MUPUS, and SESAME) provided some physical characteristics that are related to the thermal inertia: density, strength, diurnal period, and thermal conductivity (for a review, see Marshall et al (2018) and , this issue). The thermal inertia was derived from Rosetta measurements with considerable error bars.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…However, this scenario is unlikely, since the response of sublimation rates to radiation is almost immediate as seen by short (< 1 h) delays of jet outbreaks (Lai et al (2016); Shi et al (2016)) and the good agreement of inner dust structures with illumination driven dust release (Kramer & Noack (2016); Kramer et al (2018)). Measurements of VIRTIS and MIRO found that the thermal inertia is lower than 320 JK −1 m −2 s −0.5 when including the error bars (see Marshall et al (2018) for an overview). Such a small thermal inertia is not able to provide the needed phase lag of several hours of the maximum sublimation with respect to the maximum irradiation as thermal simulations show and measurements of the activity maxima compared to noon time show Shi et al (2016).…”
Section: Matching Fourier Coefficients With the Observed Torquementioning
confidence: 99%